Intervention Protocol to Address the Difficult Airway. An Alternative for the Anesthesiologist’s Performance - Fernando Márquez Ercia; José Julio Ojeda González; Bárbara Lucia Cabezas Poblet; Magda Robaina Pérez (Medisur)
Background: The ability to secure the airway in a variety of patients and clinical circumstances constitutes an essential domain for the health team. It is an everyday activity for the anesthesiologist, who is considered to be the "expert" in this area. Therefore, their cooperation is often required in Emergency Services, in Intensive Care Unities and in other areas of the hospital where medical staffs present difficulties in ventilating and / or intubating the airway of patients. Objective: To design an intervention protocol in order to address the difficult airway. Methods: An exploratory study was performed. It was supported by qualitative and quantitative methodology. Documentary analysis, observation, expert criteria and surveys to specialists were among the methods used. Results: Theoretical systematization showed that the difficulties in addressing the airway in patients undergoing surgery are a challenge in the performance of the anesthesiologist. Although many tests can predict, to a certain extent, the approach to the airway, none of them is absolutely specific. Conclusions: An intervention protocol was designed for addressing the difficult airway. It is based on needs assessment in the performance of the Anesthesiology and Reanimation Specialist. The proposed protocol was validated by experts and is an alternative that helps building a consensus and improving the performance of the anesthesiologist.